Diplomasi Pertahanan Indonesia Dalam Asean Outlook On The Indo-Pacific (AOIP) - Setyorini, Islamia Dewi; Er Abdillah, Ahmad Adam; Pahlevi, Ahmad Jidan; Bintoro, Aulia Putri; Defianti, Digna; Florens, Melvina; Rosanda, Nabilla; Qardhawi, Rafif (Department of International Relations, Brawijaya University, 2022)
Currently, the Indo-Pacific region is one of the regions that has become an important concept in international relations, especially among ASEAN countries. This happens because there is an awareness that this area is strategic in various aspects and has a positive effect on countries in the region. However, the region faces several threats, including a rivalry between two major powers, the United States and China, and the presence of territorial sovereignty claims in the region. As a result, there is a need for increased awareness and regional countries' efforts to protect the region's stability from existing influences and threats. One form of awareness of the importance of maintaining the Indo-Pacific region can be seen in the ASEAN Outlook on the Indo-Pacific (AOIP). AOIP is initiated by one of the countries in the region, namely, Indonesia, where it becomes a means of Indonesian defence diplomacy to achieve national and regional interests. This article explains how Indonesia conducts its defence diplomacy in AOIP. This article uses descriptive methods by explaining and providing an overview of existing phenomena. Based on the process of collecting data from books, journals, and related official websites that can help explain and analyse this topic, the results of this analysis prove that AOIP becomes a form of Indonesian defence diplomacy because Indonesia sees various threats present in the region that can endanger its sovereignty and even the stability of the Indo-Pacific region. Thus, in its implementation, Indonesia conducts diplomacy through cooperation with countries in the region. Keywords: AOIP, Defense diplomacy, Indonesia, ASEAN, national interest